Strategi Komunikasi Edukatif Relawan Sanggar Anak Sungai Deli dalam Meningkatkan Ibadah Anak Putus Sekolah di Pinggiran Sungai Deli Kelurahan Sei Mati Kecamatan Medan Maimun - Dina Anzani; Muktaruddin Muktaruddin; Ahmad Tamrin Sikumbang (Prodi Perpustakaan dan Sains Informasi, 2023)
This study aims to reveal how the educative communication strategy of Sanggar Anak Sungai Deli volunteers improves the worship of school dropouts on the banks of the Deli River. The research method used is a qualitative method by describing the results of the data obtained through interviews, observation, and documentation. This research was conducted at the Deli Anak Sungai Studio, Sei Mati Village, Medan Maimun District.The results of the research conducted showed that dropout children worship at the Anak Sungai Deli Studio in the form of obligatory and sunnah prayers. The fardu prayers that they do in a day and night are not performed often, most of them prefer to perform the evening prayers in congregation at the nearest musholla or at their respective homes. In addition, school dropouts also carry out worship practices such as fasting Ramadan, sunnah tarawih prayers, fardu kifayah practices, reading the Koran by holding Maghrib Koran, giving alms, and other worship practices. The increase in worship arose because of an educative communication strategy for Sanggar Anak Sungai Deli volunteers who were able to educate them with religious materials delivered, advice, directions, and in the form of information that educates the increase in the worship of out-of-school children on the banks of the Deli River.